2017
DOI: 10.1103/physrevb.95.094409
|View full text |Cite
|
Sign up to set email alerts
|

Quantum interference effects in molecular spin hybrids

Abstract: We have studied by means of low-temperature scanning tunneling microscopy (STM) and spectroscopy (STS) single molecular spin hybrids formed upon chemisorbing a polycyclic aromatic, 3-fold symmetric hydrocarbon molecule on Co(111) nanoislands. The spin-dependent hybridization between the Co d-states and the π-orbitals of the molecule leads to a spin-imbalanced electronic structure of the chemisorbed organic molecule. Spin-sensitive measurements reveal that the spin polarization shows intramolecular variations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 77 publications
1
10
0
Order By: Relevance
“…At low temperature, the N atoms of the triazine ring adsorb on top sites of the Cu surface atoms while the centers of the peripheral phenyl groups are located on hollow adsorption sites. Similar adsorption sites of TPT molecules have recently been reported on other metal surfaces at extremely low temperatures (<5 K), ,, which is the energetically most favorable adsorption configuration for this metal–organic system. Most interestingly, this adsorption configuration clearly differs from the one of the RT phase in which the N atoms of the triazine ring are located on hollow adsorption sites and the centers of the peripheral phenyl groups on top sites.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…At low temperature, the N atoms of the triazine ring adsorb on top sites of the Cu surface atoms while the centers of the peripheral phenyl groups are located on hollow adsorption sites. Similar adsorption sites of TPT molecules have recently been reported on other metal surfaces at extremely low temperatures (<5 K), ,, which is the energetically most favorable adsorption configuration for this metal–organic system. Most interestingly, this adsorption configuration clearly differs from the one of the RT phase in which the N atoms of the triazine ring are located on hollow adsorption sites and the centers of the peripheral phenyl groups on top sites.…”
Section: Resultssupporting
confidence: 82%
“…This is only possible for an adsorption configuration with an on-top adsorption site of the peripheral phenyl groups as well as of the central triazine ring as illustrated in Figure d. Noticeably, the N atoms of trazine ring are located on highly symmetric hollow adsorption sites and not on top adsorption sites as previously observed for TPT on highly reactive Fe and Co metal surfaces. , This is particularly interesting since this top adsorption site was identified as the energetically favored adsorption configuration for TPT on metal surfaces. Our result clearly suggests that the structure formation of TPT on Cu(111) at RT is not only determined by the molecule–surface interaction but also strongly influenced by intermolecular interactions between TPT molecules.…”
Section: Resultsmentioning
confidence: 61%
“…Catalytic performances in heterogeneous catalysis are correlated with the structure and composition profile since they also tune the electronic and chemical properties of a solid catalyst. , Stability, bond distances, charge transfer, and ligand and ensemble effects , can only partially account for the enhanced activity of Pt 3 Co (111) in the ORR. Experiments demonstrate that an atom or a molecule deposited on a magnetic surface experiences charge transport as well as spin transport; , typically, the understanding of the physicochemical mechanism involved in this interaction represents the main focus of molecular spintronics. , The interface between an atom (or molecule) and a magnetic surface becomes the playground for spin-dependent hybridizations between the ferromagnet and the adsorbate, and it is referred to as the spinterface …”
Section: Resultsmentioning
confidence: 99%
“…Well-organized and oriented monolayers [36] can be formed in the process of self-assembly. On metallic substrates coated by a SAM of bio/organic molecules, the mixing of molecular and surface electronic states leads to the formation of a new hybrid state of matter that often presents novel electronic/magnetic properties, giving one the opportunity to investigate interesting (sometimes unexpected) physical effects [32,[37][38][39][40][41][42][43][44][45][46][47][48][49][50]. Among others, it has been demonstrated that bio/organic coatings can dramatically extend molecular coherent states and induce Rabi splitting.…”
Section: Introductionmentioning
confidence: 99%